Helicobacter pylori as an Initiating Factor of Complications in Patients With Cirrhosis: A Single-Center Observational Study - Abdel-Razik, Ahmed; Mousa, Nasser; Elhelaly, Rania; Elzehery, Rasha; Hasan, Ahmad S.; Abdelsalam, Mostafa; Seif, Ahmed Salah; Tawfik, Ahmed M.; El-Wakeel, Niveen; Eldars, Waleed (Frontiers in Medicine, 2020)
Background and Aim: The relationship between liver cirrhosis and Helicobacter pylori (H. pylori) is a debatable matter. The aim of this study is to evaluate the possible association between H. pylori infection and liver cirrhosis. Methods: A single-center prospective cohort pilot study of 558 patients with cirrhosis was followed up for 1 year. Serum C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), nitric oxide (NO), vascular endothelial growth factor (VEGF) levels and Fecal H. pylori antigen were evaluated by enzyme-linked immunosorbent assay (ELISA). All patients with positive H. pylori were treated and then followed up for 3 months. Participants with eradicated H. pylori were followed up for one further year. Results: H. pylori-positive patients (48.4%) were associated with increased levels of serum CRP, TNF-α, IL-6, NO, and VEGF, as well as increased incidence of varices, portal hypertensive gastropathy, gastric antral vascular ectasia, hepatocellular carcinoma (HCC), spontaneous bacterial peritonitis, hepatic encephalopathy, portal vein thrombosis (PVT), and hepatorenal syndrome (all P<0.05). Multivariate analysis models revealed that the presence of H. pylori was an independent risk variable for the development of portal vein thrombosis and hepatocellular carcinoma (P=0.043, P=0.037) respectively. After treatment of H. pylori infection, there was a significant reduction in all measured biochemical parameters and reported cirrhotic complications (all P<0.05). Conclusion: Incidence of PVT and HCC development increased with H. pylori infection through increased inflammatory markers and vascular mediators. Moreover, its eradication may reduce the incidence of these complications.